Stability of biochemical constituents conserved in two types of primary tubes: study by the combined criterion of analytical and biological variability - Saldaña Orejón, Italo Moisés (2018)
Mr. Editor The delay in the measurement of a biochemical magnitude can cause errors in the interpretation of the results due to the variation of the components of the sample, for this reason we want to share a study whose objective was to determine the stability of 27 biochemical constituents conserved at temperature of refrigeration in two types of primary tubes, assessed by the combined criterion of analytical and biological variability.